Spiritual Capacity Development Training Model Students in Realizing Personal Character and Ethics - Khairul - Saleh; Hadiahti - Utami; Kurniani - Kurniani; Budi - Prasetya (Admisi dan Bisnis, 2022)
The issues being studied in this reserach was to define any appropiate model of newly recruited student’s spiritual capacity building based on Training Need Analysis. The objective of the research was to know the newly recruited students’ need to training in building their spiritual capacity and secondly to to find out the students’s actual need through three variabels; namely organizational variabel, job need variabel, and personal variabel as indicators.It was a qualitative descriptive research whose respondens classified into thre categories: management and policy maker who defines orgnisational, stakeholder and personal need, secondly, 100 respondentts from PESIMA participants and extrainers, taken by random sampling techniques. Data collection method was interview to management and questioanire distributed to participants and extrainer of PESIMA. Discussion scheme was adjusted with TNA model while analytic model was Iimportance Performance Analysis (IPA) techniques.The outcome of this research was normative model based on Training Needs Analysis (TNA) and Scientific journal publication. In addition there was additional Training TOR for Students’ Spiritual Building / PESIMA TNA bases. It was concluded that PESIMA, which was conducted for 18 years, in general it has insufficient performance level, or the students’ satisfaction was considered low. On the other hand their expectation level to this training was classified into high. It was reflected from the low level of average score index. The mostly expected indicator or the Highest Level of Importance was pasca training (follow up) guidance. With the score index of 82,8. Training was asssumed as less powerfull to provide any supplies/basic capitals for students to face industrial 4.0 challenges